Development of Electronic Modules (MOLEK) in Learning to Write Poetry at MTS Nurrodiyah Kota Baru Jambi - Sholeha, Puji; Nazurty; Rustam (Graduate Program Magister Manajemen Pendidikan, 2025)
This study aims to develop teaching materials and describe the effectiveness of electronic modules (MOLEK) in improving poetry writing skills in class VIII MTs Nurrodiyah Kota Baru Jambi. The research method used is research and development. The development procedure in this study used the research and development design of the ADDIE model (Analysis, Design, Development, Implementation, Evalution). Data collection techniques in this study are divided into two, namely during pre-research (interviews and observations) and during research (questionnaires and student learning outcomes tests). The calculation of the validity of the instrument items for the test was carried out by calculating the correlation between the item score and the total instrument score using the Pearson product moment correlation coefficient formula. The results are that the electronic module developed is suitable for use in learning and the use of this Electronic Module (Molek) is proven effective in improving students' poetry writing skills and learning interest.